Discovery of an M-type companion to the Herbig Ae Star V1787 Ori. Issue 1 (24th November 2020) - Arun, R; Mathew, Blesson; Rengaswamy, Sridharan; Manoj, P; Narang, Mayank; Kartha, Sreeja S; Maheshwar, G
ABSTRACT: The intermediate-mass Herbig Ae star V1787 Ori is a member of the L1641 star-forming region in the Orion A molecular cloud. We report the detection of an M-type companion to V1787 Ori at a projected separation of 6.66 arcsec (corresponding to 2577 au), from the analysis of VLT/NACO adaptive optics K s -band image. Using astrometric data from Gaia DR2, we show that V1787 Ori A and B share similar distance ( d ∼ 387 pc) and proper motion, indicating that they are physically associated. We estimate the spectral type of V1787 Ori B to be M5 ± 2 from colour–spectral type calibration tables and template matching using SpeX spectral library. By fitting PARSEC models in the Pan-STARRS colour–magnitude diagram, we find that V1787 Ori B has an age of 8.1^+1.7_-1.5 Myr and a mass of 0.39^+0.02_-0.05 M⊙ . We show that V1787 Ori is a pre-main-sequence wide binary system with a mass ratio of 0.23. Such a low-mass ratio system is rarely identified in Herbig Ae/Be binary systems. We conclude this work with a discussion on possible mechanisms for the formation of V1787 Ori wide binary system.